Influence of surface roughness on Ge nanowire growth by MBE. Issue 10 (6th August 2013) - Bansen, Roman; Schmidtbauer, Jan; Juda, Uta; Markurt, Toni; Teubner, Thomas; Heimburger, Robert; Boeck, Torsten
Abstract <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Significant substrate‐dependent variations in germanium nanowire (NW) growth by molecular beam epitaxy (MBE) were found, although nominally identical substrates were used. To investigate this phenomenon, the surfaces of Ge(111) wafers polished with different polishing cloths and different pressures during planarization were studied. Characterization by means of atomic force microscopy (AFM), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed differences in surface roughness, which has an influence on the respective catalyst droplets' areal densities. These differences, however, manifest on larger scales and can only be determined by statistical evaluation of sufficiently large areas on the sample. This led to the conclusion, that even minor surface irregularities from chemical‐mechanical polishing (CMP) on otherwise atomically flat substrates can have a paramount influence on NW growth, if the scale on which these irregularities occur matches the scale or distance of the used catalyst droplets. It is assumed that small protrusions on the surface serve as pinning points to the droplets. This behavior promotes the vertical growth of NWs and avoids lateral movement of droplets or classical island formation. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)